Sustainability indicators - a tool for regional co-operation - Heike Koitka (European Regional Science Association (ERSA), 2002)
Sustainability indicators are more than just numbers. Besides their main function of illustrating the complex vision of sustainability they could support some factors for success of regional co-operation through their development. Today the discussion on indicators and co-operation is mainly separated from each other. Sustainability indicators are developed on all spatial levels from neighbourhoods up to the United Nations. In some cases the indicators are developed but remain unused. Regional co-operations on sustainability are more or less successful. Some fail because of the complexity of the topic and the multitude of people involved in sustainability. Despite the existing problems the necessity of both topics for the implementation of sustainable development is out of question. Some of the problems mentioned could be solved by the linkage of the two topics: indicators are not developed as an end in itself and regional co-operation could become more successful. The improvement of both is possible because important factors for success of co-operation can be supported by the following abilities resulting from the development of indicators: a) consensus building, b) improvement of the quality of basic information, c) definition of quantified aims and priorities, d) comprehensive development of measures, e) recognition of need for action f) evaluation of success. Besides these effects among the co-operating actors indicators development supports the following factors according to the external of the co-operation: g) information on the work of the co-operation (setting up transparency), h) contribution to a new sustainable awareness. Additionally the indicators are enhanced because the people developing and using them have intellectual ownership of them and guarantee that they are more than numbers. Regional co-operation and sustainability indicators become one unit and could be seen as a sustainable regional management system.
Keywords: 330